Rosalyn Quest’s Social World Journey in Kayvion Lewis’s Thieves’ Gambit - Syahadatud Dinurriyah, Itsna; Akhmad Fuadie, Latief (Alphabet, 2025)
This study explores adolescent experience in young adult fiction, focusing on the tension between strict familial rules and broader social encounters through the character of Rosalyn Quest in Thieves’ Gambit by Kayvion Lewis. Raised under the maxim “A Quest can’t trust anyone in this world – except for a Quest,” Rosalyn’s carefully examined her interpretive framework about human relationship (stock of knowledge). Her stock of knowledge faces systemic destabilization when she is forced to navigate in high-stakes situations that require negotiation, collaboration, and risk-taking with strangers. The researcher uses a qualitative-descriptive method with the purpose of exploring Rosalyn Quest‘s rigid typification (categorial understanding of others as a threat) undergo phenomenological crisis through repeated contradictory experiences of genuine cooperation and reciprocal vulnerability. The study demonstrates her gradual development of intersubjectivity, from recognising other as competitors until turned into teammates. Rosalyn's motivational shift from because-motives (actions determined by past traumas) to in-order-to motives (self-chosen future goals), began in her rejection of kidnapping assignment and creating alternative solution based on autonomous ethical commitments. The revelation that her foundational trauma was orchestrated by her mother complete collapsed her lifeworld, forcing meaning reconstruction on new foundations. Rosalyn's concluding principle, "trust no one" and maintained relationships, represents not regression but advance synthesis acknowledging the possibility of betrayal and authenticity. This study extends phenomenological approaches to young adult fiction by interpreting Thieves’ Gambit as a narrative of consciousness development, where growth arises not from achieving certainty but from learning to navigate ambiguity, sustain intersubjective awareness, and enact authentic agency within limits. Through this, the novel implicitly educates readers about constructing meaning and transformation amid uncertainty and betrayal.